(untitled) (Castilla. Estudios de Literatura, 2011)
The different layers that make up The Ingenious Gentleman Don Quixote of La Mancha, have in its own way the key to understanding the development of modern narrative, providing the reader with a double vision. While the first one is aimed to a tragic cosmic visualization full of pain and disappointment, the second one creates a comic universe dominated by chance, where society’s habits are mocked about. Albeit these two life-choice options appear to be opposite to each other, we will benefit from the different readings and meanings of this novel to find out about how these two perspectives complement each other. To such end, Cervante’s characters and scenarios will be compared with more recent references both in time and judgement.